Ion‐Exchange Strategy for Metal‐Organic Frameworks‐Derived Composites with Tunable Hollow Porous and Microwave Absorption. Issue 9 (8th June 2022) - Tao, Jiaqi; Tan, Ruiyang; Xu, Linling; Zhou, Jintang; Yao, Zhengjun; Lei, Yiming; Chen, Ping; Li, Zhong; Ou, Jian Zhen
Abstract: Hollow metal‐organic frameworks (MOFs) with careful phase engineering have been considered to be suitable candidates for high‐performance microwave absorbents. However, there has been a lack of direct methods tailored to MOFs in this area. Here, a facile and safe Ni 2+ ‐exchange strategy is proposed to synthesize graphite/CoNi alloy hollow porous composites from Ni 2+ concentration‐dependent etching of Zeolite imidazole frame‐67 (ZIF‐67) MOF and subsequent thermal field regulation. Such a special combination of hollow structure and carefully selected hybrid phase are with optimized impedance matching and electromagnetic attenuation. Especially, the suitable carrier transport model and the rich polarization site enhance the dielectric loss, while more significant hysteresis loss and more natural resonance increase the magnetic loss. As a result, excellent microwave absorbing (MA) performances of both broadband absorption (7.63 GHz) and high‐efficiency loss (‐63.79 dB) are obtained. Moreover, the applicability and practicability of the strategy are demonstrated. This work illustrates the unique advantages of ion‐exchange strategy in structure design, component optimization, and electromagnetic regulation, providing a new reference for the 5G cause and MA field. Abstract : The facile ion‐exchange strategy is provided to regulate the structure and microwave absorbing performance of the metal‐organic frames derivative. Specifically, not only the Ni 2+ concentration is adjusted to get a suitable cavity, but also the components, interfaces, defects, and polar groups are improved by thermodynamic regulation, thus achieving enhanced performance that results in the best impedance matching and electromagnetic attenuation.